Pengaruh Gaya Humor dan Komunikasi Positif Terhadap Keterampilan Interpersonal Mahasiswa Calon Guru - Umar, Nur Fadhilah; Pandang, Abdullah; Fitri, Qawiyyan (Jurnal Studi Guru dan Pembelajaran, 2024)
The purpose of this study is to measure the impact of humor style and positive communication on interpersonal skills among university students in three provinces in Sulawesi through quantitative correlation analysis research. The sample consisted of 389 university students from South Sulawesi, West Sulawesi, and Central Sulawesi. The measuring instrument used was a questionnaire analyzed by confirmatory factor analysis (CFA) using JASP software between the variables of humor style (X1), positive communication (X2) and interpersonal skills (Y). The findings of this study, obtained from descriptive and regression tests, show that students who apply positive communication tend to have a more effective impact on their interpersonal skills. In addition, humor style in positive communication patterns has a significant influence on the success of one's communication. Therefore, it can be concluded that positive communication with elements of humor in interactions is very important to improve one's interpersonal skills in various aspects of student life.